PREELIMINARY STUDY: WATER QUALITY PARAMETER ANALYZES OF SALT EVAPORATION PONDS IN KECAMATAN GALIS KAB. PAMEKASAN, EAST JAVA - Jayanthi, Onie Wiwid (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2020)
AbstractWater quality is an important parameter that affects the productivity and quality of salt produced in the traditional salt ponds. Environmental factors of water quality in salt ponds include bouzem plots, brine plots, peminihan ponds, and crystallization tables are important to be analyzed so that the quality of community salt can be improved, but some research is very limited about this so this research needs to be carried out. The method that used in this research is exploratory descriptive method by measuring water quality in bouzem plots, brine plots, evaporation ponds and crystallization tables. The result of water quality in bouzem plots (temperature=32ᴼC; pH=8,5; DO = 5,2 mg/L; salinity=2,5ᴼBe), evaporations ponds (temperature=34ᴼC ; pH=8,5 – 8,6 ; DO=5,4 – 6,2 mg/L; salinity=34ᴼBe), brine plots (temperature=39ᴼC ; pH=7,4 – 7,5 ; DO=2,8 – 3,3 mg/L; salinity=20ᴼBe), and crystallization tables (temperature=38ᴼC ; pH=5,7 – 6,4 ; DO=1,2 – 1,3 mg/L; salinity=29ᴼBe) Keywords: Water quality, Salt Evaporation Ponds, Pamekasan